(untitled) (Jurnal Ilmiah Sains dan Teknologi, 2019)
Data from Educators, Education Personnel and Students is not important in the Serang City Education and Culture Office, operations carried out at this institution in the Educators, Education and Student Educations reports, but data collection and preparation of reports from Educators, Education Personnel along with Students used so far are still using data processing applications using manual using Microsoft Excel. This proves to be less effective and efficient in supporting employee productivity in it. Coupled with data provided from schools under the auspices of the Serang City Education and Culture Office, the old school distance was considered far apart. From these considerations raises a discussion to create an application database, which is in it to be able to manage and collect data on educators, education personnel and students. The method used in making this application is the waterfall method. The programming language is php. For display using Jquery and CSS. The database uses MysQL. The tools and editors used are XAMPP for Windows 1.7.3, Photoshop and Notepad ++. Supported by the availability of internet network within the institution. This application will be used as a media controller or data controller for Educators, Education Personnel and Students. Users themselves are divided into 2 levels, namely Administrators or Service Admin and School Users or School Admins. With the presence of Educator applications, Education Personnel and Students in data collection and processing so as to produce reports that are expected to be known easily, quickly and accurately.